Respuesta :
x^2-6-5x=0
x^2-5x-6=0
x^2-6x+1x-6=0
x(x-6)+1(x-6)=0
(x-6)(x+1)=0
x-6=0
x=0+6
x=6
x+1=0
x=0-1
x=-1
Option C
x^2-5x-6=0
x^2-6x+1x-6=0
x(x-6)+1(x-6)=0
(x-6)(x+1)=0
x-6=0
x=0+6
x=6
x+1=0
x=0-1
x=-1
Option C
Answer:
answer B: x = -1 and x = 6
Step-by-step explanation:
Rewrite x² - 6 = 5x as x² - 5x - 6 = 0, which is in standard form for a quadratic.
Factoring by grouping results in x^2 - 6x + 1x - 6. pr
x(x - 6) + 1(x - 6) = 0.
This simplifies to (x - 6)(x + 1) = 0, whose solutions are x = 6 and x = -1.
This corresponds to given answer B: x = -1 and x = 6